No food security without food safety: Lessons from livestock related research - Vipham, J.L.; Amenu, K.; Alonso, Silvia; Ndahetuye, J.-B.; Zereyesus, Y.; Nishimwe, K.; Bowers, E.; Maier, D.; Sah, K.; Havelaar, A.; Grace, Delia (Elsevier, 2020)
Foodborne disease poses several major threats toward attaining sustainable improvements in food and nutrition security (FNS), on a global scale. These threats have numerous rippling effects on public health, economic growth, and country development. This article—based on a review of literature and experience from the United States Agency for International Development (USAID) Feed the Future Innovation Lab for Livestock Systems (LSIL) research activities—seeks to explore and summarize current and ongoing efforts to improve safety of animal-source foods, as well as to identify the interconnected elements of food safety and FNS. This article focuses on emerging evidence for the disease and economic burdens of foodborne disease; source attribution; previous investments in food safety; and current challenges and opportunities.